Communication Activities of the "Sehati Selalu" Waste Bank in Cakung District, East Jakarta - Saktisyahputra Saktisyahputra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Garbage is a widespread issue throughout the world, particularly in Indonesia. The problem of waste, particularly in Indonesia as a developing country, requires more attention as the rate of population growth continues to rise. According to various media reports, Bantar Gate, the final waste disposal site, will be completely full and unable to accept any more waste within the next five years. Regulation No. 77 of the Governor of the Special Capital Region Jakarta concerns on waste management within the hamlet. Researchers are interested in conducting research on Communicative Actions at Sehati Selalu Waste Bank, Cakung District, East Jakarta, using Jurgen Habermas' Communicative Action Theory. The research method in this study used the Phenomenology of Edmund Husserl. Meanwhile, observation, interviews, and documentation are all methods for gathering data. Based on the researchers' data findings, data results, and discussions, it can be concluded that the communicative action to increase community participation carried out by the “Sehati Selalu” waste bank, Cakung district, East Jakarta, is to disseminate information to the community through supervisors in the urban village with the assistance of the participation of neighbourhood, hamlet, urban village head, and subdistrict head Management as community controllers offline. Offline communication actions are also carried out through social media platforms such as Facebook and Instagram for environmental services Cakung.